2012
DOI: 10.1080/00028487.2012.683468
|View full text |Cite
|
Sign up to set email alerts
|

Movement of Radio‐Tagged Adult Pacific Lampreys during a Large‐Scale Fishway Velocity Experiment

Abstract: Optimization of fishways to pass multiple species is challenging because life history, swimming ability, and behavior often differ among species. For example, high fishway water velocities designed to attract adult Pacific salmon Oncorhynchus spp. at Columbia River dams inhibit fishway entrance and passage success of adult Pacific lampreys Lampetra tridentata, a species of conservation concern. We tested whether reduced water velocities (∼1.2 m/s, 0.15 m of head) at Bonneville Dam fishway openings improved ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 27 publications
3
43
0
Order By: Relevance
“…Thus, the streaming flow configuration is the most suitable for fishways constructed in river systems in which a wide range of fish morpho-ecological traits are found. Existing fishways should be retrofitted to accommodate the behaviour and swimming capabilities of the species present at the site [58]. The present study shows that enabling streaming flows on future and on existing fishways is desirable.…”
Section: Discussionmentioning
confidence: 91%
“…Thus, the streaming flow configuration is the most suitable for fishways constructed in river systems in which a wide range of fish morpho-ecological traits are found. Existing fishways should be retrofitted to accommodate the behaviour and swimming capabilities of the species present at the site [58]. The present study shows that enabling streaming flows on future and on existing fishways is desirable.…”
Section: Discussionmentioning
confidence: 91%
“…Fish & Wildlife Service 2010). Radiotelemetry studies have shown that more than 50% of adult Pacific lampreys fail to pass through some dam fishways despite often repeated attempts to move upstream (Moser et al 2002;Mesa et al 2010;Johnson et al 2012). Low dam passage efficiency at multiple consecutive main stem dams can result in few adults reaching interior spawning tributaries.…”
Section: Introductionmentioning
confidence: 99%
“…Most research concerning lamprey passage has originated in North America: firstly, in detailing the efficacy of large fishway facilities at hydropower dams in the lower Columbia River for threatened Pacific lamprey Lampetra tridentata (Jackson and Moser, 2012;Johnson et al, 2012;Keefer et al, 2009Keefer et al, , 2010Keefer et al, , 2011Moser et al, 2002aMoser et al, , 2002bMoser et al, , 2011, and secondly in investigating the capabilities of the sea lamprey Petromyzon marinus, an invasive species in the Great Lakes, to negotiate barriers, in order to develop preventative measures to block their upstream migration (Hanson, 1978;Hunn and Youngs, 1980;Katopodis et al, 1994). However, differences in the size, swimming capabilities and behaviour of lamprey species and migratory forms warrant care in extrapolation between species.…”
Section: Introductionmentioning
confidence: 99%